2001
DOI: 10.1111/j.1572-0241.2001.04669.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-mediated amplification is more sensitive than conventional PCR-based assays for detecting residual serum HCV RNA at end of treatment

Abstract: Residual serum HCV RNA was detected by the TMA-based assay in EOT samples from 34.6% of patients that had achieved apparent viral clearance by PCR. The detection of HCV RNA by the TMA-based assay could help redefine EOT response and assist in the antiviral management of HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 8 publications
1
34
1
1
Order By: Relevance
“…The specimen was considered reactive, or having detectable HCV RNA, when the signal-to-cutoff ratio was greater than one. The technology and performance of the assay has been previously well described (Comanor et al, 2001;Gorrin et al, 2003;Hendricks et al, 2003;Sarrazin et al, 2000).…”
Section: Hcv Rna Detection By Tmamentioning
confidence: 99%
“…The specimen was considered reactive, or having detectable HCV RNA, when the signal-to-cutoff ratio was greater than one. The technology and performance of the assay has been previously well described (Comanor et al, 2001;Gorrin et al, 2003;Hendricks et al, 2003;Sarrazin et al, 2000).…”
Section: Hcv Rna Detection By Tmamentioning
confidence: 99%
“…However, the TMA may be more sensitive than the PCR, while maintaining the same high specificity [85]. The TMA is a ultrasensitive HCV RNA qualitative assay that can detect minute amounts HCV RNA [85,[93][94][95][96][97][98]. Since TMA can detect fewer than 50 HCV copies/ml and less than 6 HCV International Units/ml (World Health Organization, 96/790, Geneva, Switzerland), it may allow early identification of virus replication and thorough verification of viral clearance.…”
Section: Hcv Molecular Assaysmentioning
confidence: 98%
“…The TMA specificity is reported to be 99.6%, which minimizes the risk of false positive results and increases confidence that positive results reflect true viremia. Several studies have shown the utility of the TMA in detecting HCV infection in the general population [85,93,97]. Krajden et al [97] examined 300 specimens including 112 samples that were indeterminate via EIA but PCR negative, and 79 samples that were EIA positive and PCR negative.…”
Section: Hcv Molecular Assaysmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, the transcription-mediated amplification (TMA) method was approved for detection of HCV RNA. TMA is a nucleic acid amplification method relying on reverse transcriptase and T7 RNA polymerase to make multiple RNA copies of an RNA template [3,4]. The sensitivity of TMA is 96 and 100% at 5 and 10 IU/ml, respectively, irrespective of HCV genotype [2].…”
Section: Introductionmentioning
confidence: 99%